Estudio de factibilidad para la implementaciòn de una planta procesadora de Cerveza Artesanal en la Parroquia de Salinas Provincia de Bolivar - López Ruiz, Oscar David (2019)
The objective of this research was to carry out a "feasibility study for the implementation of a craft beer processor in the parish of Salinas" province of Bolivar In the financial study, the real investments for the assembly and operation of the craft beer processing plant were clearly determined, taking as a total investment of $ 36,034.13 dollars, it will be financed 70% by the shareholder and the remaining 30% will be a financing banking. The financial evaluation is the most important of the project where the calculations made show a NPV of $ 78,415.66, with a TMAR of 7.32% and a CAPM rate of 7.30%, obtaining a NPV of $ 81,999.52 and an IRR of 66, 14% being greater than the opportunity cost of money. The recovery of the investment is 1 year 7 months. It should be noted in Annex No. 8 is another proposal with greater investment including values such as land, buildings, vehicle, etc., with its respective financial evaluation by obtaining indicators with a lower item.